Women’s Representations in Thai Communist Publications: The Reconstruction of Female Images - Posrithong, Natanaree; Wachira-atsakon, Anchana (Thammasat Review, 2024)
The primary purpose of this research is to explore the representations of women in print media published under the influence of leftist ideologies–Marxism, Socialism and Communism–and the Communist Party of Thailand (CPT). This study aims to examine the significance of left-wing publications as channels for disseminating revolutionary ideas, focusing on the promotion of gender equality and the reconstruction of female images. Despite facing anti-communist campaigns imposed by the right-wing authorities from the 1960s to the 1980s, several publications have been archived and thus they deserve further study. The materials examined in this paper include seven selected publications: Ekkarat (Independence), Chayo Tulachai (Victorious Octoberists), Thong Rop (Warrior Flag), Prachakhom (Community), Chu Thong Rop (Raising the Warrior Flag), Phu Bukboek (The Pioneers), and Mahachon (The Masses). A closer visual and narrative analysis employing the framework of socialist gender discourse on these publications reveals multiple attempts to reconstruct representations of women, as well as female images and voices that contest the prevailing social norms and myths perpetuated by patriarchy and capitalism. These representations highlight the emergence of women as revolutionary individuals and proletarian subjects. Therefore, this paper aims to shed light on a new perspective regarding women during these often-overlooked periods